2016
DOI: 10.1016/j.jenvrad.2016.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to tritiated water at an elevated temperature: Genotoxic and transcriptomic effects in marine mussels (M. galloprovincialis)

Abstract: Temperature is an abiotic factor of particular concern for assessing the potential impacts of radionuclides on marine species. This is particularly true for tritium, which is discharged as tritiated water (HTO) in the process of cooling nuclear institutions. Additionally, with sea surface temperatures forecast to rise 0.5-3.5 °C in the next 30-100 years, determining the interaction of elevated temperature with radiological exposure has never been more relevant. We assessed the tissue-specific accumulation, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…Mussels were transferred to 2 L glass beakers 48 h prior to exposure at a density of 4.5 mussels L -1 (i.e. 9 mussels -1 beaker) in order to acclimate and in line with our previous study (Dallas et al, 2016b). Nine mussels were exposed to one of 8 treatments (Figure 1), comprising a seawater-only control, 383, 1915 or 3830 nM Zn, and 4 treatments containing 5 MBq L -1 HTO, which has previously shown consistent genotoxic effects in haemocytes across numerous experiments [Jha et al, 2005;Jaeschke et al, 2011;Dallas et al 2016 a].…”
Section: Mussel Maintenance and Experimental Designmentioning
confidence: 99%
“…Mussels were transferred to 2 L glass beakers 48 h prior to exposure at a density of 4.5 mussels L -1 (i.e. 9 mussels -1 beaker) in order to acclimate and in line with our previous study (Dallas et al, 2016b). Nine mussels were exposed to one of 8 treatments (Figure 1), comprising a seawater-only control, 383, 1915 or 3830 nM Zn, and 4 treatments containing 5 MBq L -1 HTO, which has previously shown consistent genotoxic effects in haemocytes across numerous experiments [Jha et al, 2005;Jaeschke et al, 2011;Dallas et al 2016 a].…”
Section: Mussel Maintenance and Experimental Designmentioning
confidence: 99%
“…Adult MG and DP were collected from Trebarwith strand (Dallas et al, 2013) and Bude, Cornwall, UK (50.828059, -4.549053), respectively. Maintenance of the mussels has been described in detail in previous publications (Dallas et al 2013;Dallas et al 2016a;Pearson et al 2018). As Hilbish et al (2002) reported the occurrence and distribution of Mytilus edulis, M. galloproviancialis and their hybrids in the coastal regions of south-west England, we ensured species homogeneity in our experiments based on the method of Inoue et al (1995).…”
Section: Mussel Exposure Conditionsmentioning
confidence: 90%
“…Activity concentrations in water were calculated from preliminary experiments (data not included). Water changes (50 %) were carried out on days 3, 5, 7 and 9 and mussels were fed during this exposure (2 hours before each water change), as described in detail elsewhere (Dallas et al 2016a). MG were fed a solution of Isochrysis galbana algae (1.05 x 10 -5 cells mL -1 , Reed Mariculture, Campbell, CA, USA), DP fed on dried Chlorella powder (3.2 mg/mussel per feed, Naturya, Bath, UK).…”
Section: Mussel Exposure Conditionsmentioning
confidence: 99%
See 2 more Smart Citations